Muddy Waters: Critiquing the Historical Criminology Method in the Investigation of the Smiley Face Murders Theory - Bleakley, Paul (Homicide studies, 2021)
As an emerging trans-disciplinary field, the operational use of historical criminology is a largely under-studied area. Examination of the use of archival research in studying cases connected to Gannon and Gilbertson’s Smiley Face murders theory indicates that there is clear potential for historical criminology to be used to revisit closed or cold investigations to determine if the official findings of the case are consistent with the evidence. In the case of the Smiley Face murders theory, taking a historical criminology approach has failed to prove the hypothesis of researchers; nevertheless, use of historical research methods has had some success in forcing a re-evaluation of several cases, and should be considered an important tool in future investigations of this nature.